On the possibilities of subject indexing in complement infinitive clauses (based on material from German and other related languages) - Денчева, Емилия (Списание „Германистика и скандинавистика“ / Journal for German and Scandinavian Studies, 2024)
The article deals with ways of encoding the subject of infinitive clauses in a number of Indo-Germanic languages. There are claims that infinitive clauses never have their own subject, but that this is implied by a part of the main clause. What infinitive clauses don’t actually have is their own syntactic position for the subject. Because with them the verb phrase is formulated in infinite terms and the congruence between subject and verb cannot be established. However, the loss of the infinite verb’s ability to exercise direct control over the carrier/recipient of the action expressed by it is not accompanied by a loss of the logical-semantic connection with it. The results of the study make it clear that this relation is always present, i.e. the subject of the infinitive is always referentially clear. The only difference is that in the Germanic languages, but also in the Romance and Slavic languages, which have an infinitive with clearly defined verbal behavior, there are complex sentence structures whose infinitive complement contains an implicit subject and those which contain an explicit subject. In the first case, it is a PRO subject that is lexically suppressed and is signaled by a referentially identical subject or object noun phrase in the superordinate structure (= antecedent). In the second case, however, the subject of the infinitive appears to function on a morphosyntactic level as a constituent (subject or object) of the main clause, but is logically and semantically connected only to the subordinate infinitive and is accordingly explicitly signaled. These are the so-called aci-, nci– and dci-constructions.